2007
DOI: 10.1007/s10529-007-9391-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of three cDNAs encoding omega-3 fatty acid desaturases from Descurainia sophia

Abstract: Three cDNAs of DsFAD3, DsFAD7 and DsFAD8, encoding omega-3 fatty acid desaturases, which are the key enzymes for the conversion of linoleic to alpha-linolenic acid (18:3n-3), were isolated from Descurainia sophia using RACE-PCR. Tissue-specific expression analysis revealed that DsFAD3 and DsFAD7 genes were expressed in all tissues and at a high level in stems, leaves and young siliques, whereas DsFAD8 was moderately expressed in photosynthetic tissues including stems, leaves and young siliques. All three genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
5
20
0
1
Order By: Relevance
“…Three replicates were averaged and the standard deviation is shown in cotton (Kargiotidou et al 2008), PoleFAD2 in purslane (Teixeira et al 2009) and PlFAD2 in Phaseolus lunatus (Zhang et al 2011) were induced by cold stress. FAD8 was also induced by low temperatures in A. thaliana (Gibson et al 1994), maize (Berberich et al 1998), rice (Wang et al 2006), Descurainia sophia (Tang et al 2007) and purslane (Teixeira et al 2010). Our results showed that there was a greater expression of two FAD genes during 6°C treatment in fingered citron leaves (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Three replicates were averaged and the standard deviation is shown in cotton (Kargiotidou et al 2008), PoleFAD2 in purslane (Teixeira et al 2009) and PlFAD2 in Phaseolus lunatus (Zhang et al 2011) were induced by cold stress. FAD8 was also induced by low temperatures in A. thaliana (Gibson et al 1994), maize (Berberich et al 1998), rice (Wang et al 2006), Descurainia sophia (Tang et al 2007) and purslane (Teixeira et al 2010). Our results showed that there was a greater expression of two FAD genes during 6°C treatment in fingered citron leaves (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Hydropathy analysis of CmsFAD2 predicted that the polypeptide contained four putative membrane-spanning (Tang et al 2007;Teixeira et al 2009). Inspection of both sequences revealed the presence of eight highly conserved histidine residues in three separate clusters, i.e.…”
Section: Isolation and Characterization Of Cmsfad2 And Cmsfad8 From Fmentioning
confidence: 99%
See 1 more Smart Citation
“…So kann es eigentlich nicht verwundern, dass einige Forschergruppen damit begonnen haben, u. a. auch die langkettigen Omega-3-Fettsäuren in transgenen Pflanzen synthetisieren zu lassen und damit einen -aus Sicht der Initiatoren -nachhaltigen, umweltverträglichen und kostengünstigen Weg zu beschreiten (Drexler et al, 2003;Dyer und Mullen, 2005;Graham et al, 2007;Kinney, 2006;Napier et al, 2004;Truska et al, 2006;Tang et al, 2007;Wu et al, 2005).…”
Section: Ein (Potentielles) Zukünftiges Versorgungsdilemma Und Ein Weunclassified
“…Two FAD3 desaturase genes were identified in flax (LuFAD3A and LuFAD3B) (Vrinten et al, 2005) and periila (PfFAD3A and PfFAD3B), which control the level of linolenic acid in seeds (Kim et al, 2008). Genes encoding plastidial ω-3 desaturases (FAD7/8) were isolated from Arabidopsis thaliana (Iba et al, 1993;Gibson et al, 1994), Glycine max (van de Loo and Somerville, 1994), Zea mays (Berberich et al, 1998), and Descurainia sophia (Tang et al, 2007). Regulation of these genes has been shown to constitute a successful strategy for modifying the PUFA content of plant lipids.…”
Section: Introductionmentioning
confidence: 99%